Does selection for gamete dispersal and capture lead to a sex difference in clump water‐holding capacity?. Issue 8 (18th August 2016) - Moore, Jonathan D.; Kollar, Leslie M.; McLetchie, D. Nicholas
Abstract : PREMISE OF THE STUDY: Differences in male and female reproductive function can lead to selection for sex‐specific gamete dispersal and capture traits. These traits have been explored from shoot to whole plant levels in wind‐pollinated species. While shoot traits have been explored in water‐fertilized species, little is known about how whole plant morphology affects gamete dispersal and capture. We used the dioecious, water‐fertilized plant Bryum argenteum to test for differences in clump morphology and water‐holding characteristics consistent with divergent selection. We hypothesized that sex‐specific clump morphology, arising at maturity, produces relatively low male water‐holding capacity for gamete dispersal and high female capacity for gamete capture. METHODS: We measured isolated young shoot and clump water‐holding capacity and clump morphological characteristics on greenhouse‐grown plants. Young shoot capacity was used to predict clump capacity, which was compared with actual clump capacity. KEY RESULTS: Young male shoots held more water per unit length, and male clumps had higher shoot density, which extrapolated to higher clump water‐holding capacity. However, female clumps held more water and were taller with more robust shoots. Actual clump capacity correlated positively with clump height and shoot cross‐sectional area. CONCLUSIONS: The sex difference in actual clump capacity and its unpredictability from younger shoots are consistent with our hypothesis that males should hold less water than females to facilitate sexual reproduction. These results provide conceptual connections to other plant groups and implications for connecting divergent selection to female‐biased sex ratios in B. argenteum and other bryophytes.